IN VITRO EVALUATION OF THE ANTI-INFLAMMATORY POTENTIAL OF ETHANOL EXTRACT FROM PINK CHRYSANTHEMUM (CHRYSANTHEMUM MORIFOLIUM) - Gloria Prisca Susana Angelique Baya; Aaltje Ellen Manampiring; Fatimawali Fatimawali; Hermina Budiarso; Billy Johnson Kepel (Riviera Publishing, 2025)
Inflammation is the body's normal response to injury. However, acute and chronic inflammatory reactions can lead to various diseases. Nonsteroidal anti-inflammatory drugs (NSAIDs) have been proven effective as anti-inflammatory agents, but excessive and long-term use of NSAIDs can cause various side effects. Pink chrysanthemum flowers (Chrysanthemum morifolium) are one of many medicinal plants used as traditional medicine due to their content of compounds such as flavonoids, triterpenoids, and steroids, which have anti-inflammatory properties and the potential to serve as alternatives to NSAIDs. To identify active compounds and analyze the anti-inflammatory activity of ethanol extract from pink chrysanthemum flowers (Chrysanthemum morifolium). This study is an experimental laboratory research. The extraction method used was Microwave-Assisted Extraction (MAE). The anti-inflammatory activity of the ethanol extract of pink chrysanthemum flowers was measured using the red blood cell membrane stabilization method. The tests were performed using a UV-Vis spectrophotometer at extract concentrations of 50 ppm, 100 ppm, 200 ppm, 400 ppm, and 800 ppm. Pink chrysanthemum flowers contain several phytochemical compounds, including alkaloids, flavonoids, tannins, triterpenoids/steroids, and phenolics. The anti-inflammatory activity measurement showed that higher extract concentrations resulted in lower absorbance values and increased stabilization percentages, indicating anti-inflammatory activity that protects red blood cell membranes from damage. The ethanol extract of pink chrysanthemum flowers contains several phytochemical compounds with potential anti-inflammatory activity. The extract at a concentration of 800 ppm demonstrated the highest membrane stabilization ability, with a stabilization rate of 59.459%.